In vitro infection of human hepatoma (HepG2) cells with hepatitis B virus. - Bchini, R (1990)
An in vitro system for production of hepatitis B virus (HBV) was established by infection of human hepatoma (HepG2) cells. HBV particles obtained from the serum of a chronic hepatitis B surface antigen (subtype ad) carrier were used to inoculate HepG2 cells. HBV envelope and core proteins were synthesized de novo by the infected cells and secreted into the medium 3 to 6 days postinfection. Viral covalently closed circular DNA, the putative template for viral RNA transcription, accumulated in the cells with increasing time postinfection. The HBV-infected HepG2 cells were maintained for several months (HepG2-BV cell line) and continued producing viral antigens. Both HBV DNA replicative intermediates and major HBV transcripts were identified in HepG2-BV cells. Complete HBV particles, which contain HBV DNA and DNA polymerase activity and express the three antigenic specificities of the envelope (hepatitis B surface antigen, pre-S2, and pre-S1), were released into the culture supernatant. Thus, successful in vitro infection of transformed human hepatocytes raising stable HBV-producing cells was achieved for the first time. This strongly suggests that HepG2 cells have a receptor(s) for virus attachment and penetration. Such a system represents a significant advance for the study of HBV-target cell interactions as the early events of HBV infection.